Knowledge and Attitude of patients about the use of surrogacy as treatment method of infertile couples - Mostafa Khomeini hospital in 2016 - Kobra Khajavi Shojaee; Ali Davati; Shahrzad Hadavand; Movahed Bahrami (Mashhad University of Medical Sciences, 2017)
Introduction: Infertility threatens the mental health of infertile couples. Society should have sufficient knowledge of the implanted embryo resulted of in vitro fertilization in the surrogacy as a therapy method. This study was performed with aim to determine the knowledge and attitude of patients in Mostafa Khomeini hospital on the use of surrogacy as a treatment method. Methods: This cross-sectional and analytic study was performed on 216 patients referred to Mostafa Khomeini Hospital in 2016. Data collection tool was a researcher-made questionnaire consisting of two parts: the first part was demographic questions and the second part included the questions about knowledge and attitude. Data were analyzed by SPSS software (version 16) and statistical tests of correlation test, independent t-test, Mann-Whitney, Kruskal wallis and ANOVA. PResults: 185 subjects (85.6%) stated that they have information about surrogacy. While according to the results, only 31 subjects (14.8%) had good and very good knowledge of surrogacy. 99 subjects (43.5%) had no religious perception about this method. 90 (41.7%) had negative attitude to the priority of surrogacy from family and friends. 144 (66.7%) agreed about insurance protection. Independent t-test showed that the mean attitude of men and women was not different. ANOVA showed a significant difference between the attitudes of subjects in different educational groups (P=0.04). Conclusion: Most people had negative attitude toward emotional, legal, and religious issues of surrogacy, but they had positive attitude to solve problems and financial costs and insurance support.